A12 Mitochondrial proteome analysis of R6/2 mouse brains. (16th November 2010) - Fleischer, C; Lehnert, S; Jahn, O; Otto, M; Landwehrmeyer, G B; Lindenberg, K S
Abstract : Background: Several observations indicate that mitochondrial dysfunction plays an important role in the pathogenesis of Huntington's disease (HD). HD patients lose significant body weight despite normal or increased food intake and impairment of ATP synthesis occurs even in pre-motor manifest HD expansion mutation carriers. Alterations in mitochondrial function and structure include impairment of respiratory chain activity, decrease of Ca 2+ buffering capacity and an increase in size of mitochondria. Until now the molecular mechanisms linking mutant huntingtin to mitochondria dysfunction are not known. Aim: Purify mitochondria from brain and skeletal muscle of two HD mouse models and analyse the proteome using a two dimensional differential in-gel electrophoresis (2D-DIGE) approach. Methods/techniques: To get a more detailed picture of mitochondrial changes in HD we isolated mitochondria of brain and skeletal muscle of the exon-1 R6/2 mouse model and of the knock-in mouse models HdhQ20/HdhQ111. First, protocols for the isolation of mitochondria using subcellular fractionation/differential centrifugation were optimised and the purity of the mitochondrial fraction was confirmed by western blot. Mitochondrial lysates were then used for proteome analysis using a 2D-DIGE approach. Results: In mitochondria of R6/2 mouse brains, mitochondrial proteins of the citric acid cycle, the amino acid degradation and mitochondria fusion were increased. Few selected mitochondrial proteins were downregulated. These results will be further corroborated by western blot and compared with changes in skeletal muscle and to proteome analysis of mitochondria from brain and skeletal muscle in the HdhQ knock-in mice. Conclusions: These first results of a mitochondrial proteome analysis on mitochondria from R6/2 mouse brains demonstrating an increase of certain mitochondrial proteins involved in energy metabolism suggests that the observed alterations reflect at least in part compensatory changes.